Boundary element modelling of a crop irrigation problem - Li, Yifei. (2013)
Furrow irrigation method is commonly used for growing row crops in areas with low rainfall. It is desirable to model the furrow irrigation system to optimize furrow design. This project focused on modelling the steady-state two-dimensional periodic furrow irrigation system with boundary element method. The boundary element procedure to model the suction potential in the soil for general furrow shape was developed. It was then applied to solve specific problems. The numerical solutions for flat, rectangular, semicircular and parabolic furrows were obtained. The problem of flat furrow irrigation with a long rock in the soil was also investigated. The boundary element solution for flat furrow case agreed very well with the analytical solution. Solutions for other cases also showed convergence and symmetry as expected. These suggest the formulation of boundary element models was accurate.